Evaluación de la política ambiental y su incidencia en la dinámica de la cobertura vegetal de las principales cuencas abastecedoras de agua en la ciudad de Loja - Rojas Ribera, Hermel de Jesus (2023)
This research analyzed the impact of environmental policy on the state of vegetation cover of the main micro-watersheds supplying water in the city of Loja. For this purpose, shapefile information from 2000, 2008, 2014 and 2018 was used to analyze the dynamics of vegetation cover through a multitemporal analysis of the different vegetation covers. The data used (shapefile and municipal ordinances) was obtained from the Interactive Map of the Ministry of Environment, Water and Ecological Transition, the Municipality of Loja and FORAGUA. The information was processed using ARCMAP 10.8 software. The results showed that in the period 2008 - 2014 the Jipiro microwatershed presented a change from 113.41 hectares of agricultural mosaics to Forest, while the El Carmen micro-watershed from 71.18 hectares of pasture to herbaceous vegetation this due to the "Ordinance for the protection of micro-watersheds and other priority areas for the conservation of Loja canton". However, the reform of the ordinance for the period 2014 - 2018 showed negative changes in the Jipiro, Mendieta, El Carmen, San Simón and Curitroje micro-watersheds, as their vegetation cover changed from forest, herbaceous vegetation, grassland, forest plantation and paramo to agricultural mosaic, with the Jipiro micro-watershed being the most affected, which changed in this period 222. 62 ha of forest, pasture, forest plantation, shrub vegetation and herbaceous vegetation to agricultural and livestock mosaic. This research work allowed us to understand the influence of environmental policies that favor the protection and maintenance of water sources such as micro-watersheds. Key words: micro-watersheds, NDVI, environmental policies, vegetation change.